When is a sentence manifestly excessive?. (December 2022) - McGorrery, Paul; Weatherson, Matthew
The most common basis for sentence appeals in Victoria is that the original sentence, or some part of it, was manifestly excessive. To date, no empirical research has been undertaken examining the bounds of manifest excess. When is a sentence not just excessive, but manifestly so? This article fills that gap by examining 100 successful manifest excess sentence appeals between 2014 and 2020, finding that the minimum reduction in a manifestly excessive sentence is about 10 per cent, but that even then, such small reductions are rare and usually in the context of sentences of four years or more.